Biology Education Across the Life Course: A Qualitative Exploration of Learning Trajectories, Transitions, and Meaning-Making - Elizabeth Ndekumwa Ngololo; Bernard Dione; Sangeeth; Anita Wulandari (WISE Pendidikan Indonesia, 2025)
This study explores biology education from a life course perspective by examining how learning trajectories, educational transitions, and meaning-making processes evolve across different stages of individuals’ lives. Drawing on qualitative methodology, the study employed in depth, semi structured life history interviews with purposively selected participants who had engaged in biology education at various educational stages. Data were analyzed using thematic narrative analysis informed by life course theory to identify patterns of continuity, change, and critical turning points in participants’ educational experiences. The findings reveal that early encounters with biology education play a foundational role in shaping long-term learning trajectories, while educational transitions particularly between secondary, higher education, and post formal contexts function as pivotal moments that can redirect engagement with biology either positively or negatively. Furthermore, the study demonstrates that the significance of biology education is not fixed during formal schooling but often reconstructed later in life as individuals integrate biological knowledge into personal, social, and professional contexts. These results suggest that biology learning outcomes may emerge cumulatively and longitudinally rather than immediately following instruction. The study contributes to the literature by bridging life course studies and biology education research, offering a novel qualitative perspective on biology learning as a developmental and contextually embedded process. The implications of this research highlight the need for biology education practices and policies that emphasize continuity, relevance, and contextual meaning-making across educational stages, thereby supporting sustained engagement with biological knowledge throughout the lifespan.